Terapi Musik Efektif terhadap Penurunan Kecemasan pada Pasien Kanker - Nurlina Nurlina; Yuliana Syam; Ariyanti Saleh (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effectiveness of music therapy in reducing anxiety in cancer patients. The research method is a literature review using five databases, namely PubMed, ProQuest, Science Direct, Clinicalkey, and Google Scholar, using keywords based on PICO. The results showed that the five articles analyzed all articles reported that music therapy effectively reduced anxiety in cancer patients. Music has psychological, physical, social, and spiritual effects that can increase support for cancer patient care, improve mood, and improve the quality of life of cancer patients to provide nursing interventions to reduce anxiety. In conclusion, music therapy is an effective therapy to reduce anxiety from children, adults to the elderly. Keywords: Cancer, Anxiety, Music Therapy